### Answered by answersmine:

Honey that is so confusing

## Related questions in Mathematics

### 78 correct answers out of 100 test questions 39 correct answers out of 50 test questions

So what is your questions

### A spotlight on the ground shines on a wall 12 m away. If a man 2 m tall walks from the spotlight toward the building at a speed of 1.9 m/s, how fast is the length of his shadow on the building decreasing when he is 4 m from the building? (Round your answer to one decimal place.)

12 m

-4 m

____

8 m

the answer to the problem is the subtract by the 8 -4=4 isnt it the work to show

-4 m

____

8 m

the answer to the problem is the subtract by the 8 -4=4 isnt it the work to show

### 3-3x6+2= we have 3 answers so far -17 -13 2 any idea's on which is correct

-13 In England we remember the order with the word BODMAS. Brackets,Of,Divide, Multiply, Add and lastly Subtract

### Amy Is training for a half marathon. In practice, she runs 2 miles in 15 minutes. If she continues at the same rate, how many miles will she run in 1 hour ? Please answer! ❤️️❤️️

Since an hour is 60 minutes, divide 60 by 15, you get 4. since she runs 2 miles in 15 minutes, and there are four 15 minutes in 60,

2 * 4 = 8.

she will run 8 miles in a hour.

2 * 4 = 8.

she will run 8 miles in a hour.

### EXERCISE A one-year membership to a gym costs $725. The registration fee is $125, and the remaining amount is paid monthly. Define a variable. Then write and solve an equation to find how much new members pay each month.

I would say the variable is the # of months. if a member joined for 6 months they would pay the 125 registration fee and then $60.42/ month.

### Solve 60=10√y-3A.y= -39B.y= 39C.y= 39,-39D.y= -10,39

60=10√(y-3)

60²=(10√(y-3))²

3600=100(y-3)

3600=100y-300

100y=3600+300

100y=3900

y=3900/100

y=39

we have to chek the possible answer:

10√(39-3)=10√36=10(6)=60

60²=(10√(y-3))²

3600=100(y-3)

3600=100y-300

100y=3600+300

100y=3900

y=3900/100

y=39

we have to chek the possible answer:

10√(39-3)=10√36=10(6)=60

**Answer: B. y=39**### Please answer those three question

1- Three and one-hundred thousandths. Tenths

2- Five and two hundred and sixty seven thousandths. Hundredths.

2- Five and two hundred and sixty seven thousandths. Hundredths.

### Hi everybody! I hope you are doing well. I really need help on these two algebra 1 questions. I've been stuck for a whole day and I would appreciate it if it could be explained.. 1. Bradley has 3 square pieces of cardboard with each side equal to x units. For each piece, he does something different to it according to each part below:Part A: Bradley pasted rectangular strips along two adjacent sides of the cardboard to increase its length and width by y units each. What will be the change in the area of the piece of cardboard? Show your work.Part B: Bradley cut off rectangular strips from two adjacent sides of the cardboard to decrease its length and width by y units each. What will be the change in the area of the piece of cardboard? Show your work. Part C: Bradley cut off a strip from one side of the cardboard and pasted the strip on an adjacent side of the cardboard to increase its length by y units and decrease its width by y units. What will be the change in the area of the cardboard? Show your work. 2. Part A: Divide (10x^4y^3 + 5x^3y^2 - 15x^2y - 25x^2y^4) by -5x^2y. Show your work, and justify each step. Part B: How would your answer in Part A be affected if the x^2 variable in the denominator was just an x? Part C: What is the degree and classification of the polynomial you got in Part A? Even if you only have time to answer one of the questions, it would really help. Thank you so much!

These are some lengthy problems for a middle school student!

Oh well, let me see what I can do.

#1:

First off. Draw 3 Squares.

Each side will have the length/width of X.

First let's find the area of a normal square.

Because Area is Base * Height we will get this:

x*x = x^2

Part A:

Alright! So we have our square, but now they add 2 strips to both sides of this square. They tell us that the length/width has increased by y. Which means that our new side is equivalent to the following expression:

X + Y

This is due to the fact that we are simply adding a new side. We haven't multiplied our length/width. So, let's examine the new area.

(x+y)*(x+y) = (x+y)^2

Now we will actually square the expression by using the FOIL method.

F - First

O - Outer

I - Inner

L - Last

Multiply the First Terms:

x*x = x^2

Multiply the Outer Terms:

x*y = xy

Multiply the Inner Terms:

y*x = xy (yx is the same as xy)

Multiply the Last Terms:

y*y = y^2

Add them all together and we have our answer!

(The two xy's add together to form 2xy!)

We are not done here! Now we must find the Change in the Area. To do so we must subtract the new area and the old area. So! Let's get right to it. (Keep in mind the "old area" is the area of a square which has the length/width of X)

(New Area) - (Old Area)

(x^2 + 2xy + y^2) - (x^2)

Cancel out the like terms to get a final answer of... :

Part B:

Same situation as the last problem! Except in this case we will be subtracting y. So our sides now look like this:

X - Y

Area = Base*Height

Both are base and height equal x-y. So we just need to multiply them together like before.

Area = (x - y)^2

Area = (x - y)(x - y)

Multiply the First Terms:

x*x = x^2

Multiply the Outer Terms:

x*-y = -xy

Multiply the Inner Terms:

-y*x = -xy

Multiply the Last Terms:

-y*-y = y^2

Change in Area = x^2 -2xy + y^2 - x^2

Once again the x^2 will cancel out.

Part C:

This is where it becomes a bit trickier. Now we have a rectangle instead of a square.

So we have two different sides.

I'll note that it doesn't matter if you say the x-y or x+y are the length or the width. As long as they are both represented it is fine.

Area = L*W

Area = (x - y)(x + y)

Multiply the First Terms:

x*x = x^2

Multiply the Outer Terms:

x*y = xy

Multiply the Inner Terms:

-y*x = -xy

Multiply the Last Terms:

-y*y = -y^2

Change in Area = x^2 + y^2 - x^2

You can probably guess by now, but the x^2's will cancel out once again!

#2: Part A:

(10x^4y^3 + 5x^3y^2 - 15x^2y - 25x^2y^4)/-5x^2y

We need to ask a few questions to get to our answer.

Is the constant in front of the denominator (-5) divisible by all of the constants in front of all the terms in the numerator (10 + 5 - 15 - 25)?

What variables are in the denominator? (x and y are)

Do all of the terms in the numerator have x and y?

If yes, then what is the lowest power of x? (x^2)

If yes, then what is the lowest power of y? (y)

What we have here is what we need to reduce the denominator by.

So we reduce all the constants by -5. (Divide by -5)

10/-5 = -2

5/-5 = -1

-15/-5 = 3

-25/-5 = 5

Next up is the variables.

For these we simply subtract the lowest power from all of them. (In reality we are dividing them by x^2, thus reducing

x^4/x^2 = x^2

x^3/x^2 = x

x^2/x^2 = 1

x^2/x^2 = 1

Lastly the y terms.

Same deal with the x terms.

y^3/y = y^2

y^2/y = y

y/y = 1

y^4/y = y^3

Now put them all together!

Part B:

All the x terms would be increased by 1 due to being reduce one less power.

So it'll look like this:

Part C:

The Degree is 3, because the highest power is 3 (y^3). The classification for this is a Cubic Polynomial.

Oh well, let me see what I can do.

#1:

First off. Draw 3 Squares.

Each side will have the length/width of X.

First let's find the area of a normal square.

Because Area is Base * Height we will get this:

x*x = x^2

Part A:

Alright! So we have our square, but now they add 2 strips to both sides of this square. They tell us that the length/width has increased by y. Which means that our new side is equivalent to the following expression:

X + Y

This is due to the fact that we are simply adding a new side. We haven't multiplied our length/width. So, let's examine the new area.

(x+y)*(x+y) = (x+y)^2

Now we will actually square the expression by using the FOIL method.

F - First

O - Outer

I - Inner

L - Last

Multiply the First Terms:

x*x = x^2

Multiply the Outer Terms:

x*y = xy

Multiply the Inner Terms:

y*x = xy (yx is the same as xy)

Multiply the Last Terms:

y*y = y^2

Add them all together and we have our answer!

**Area = x^2 + 2xy + y^2**(The two xy's add together to form 2xy!)

We are not done here! Now we must find the Change in the Area. To do so we must subtract the new area and the old area. So! Let's get right to it. (Keep in mind the "old area" is the area of a square which has the length/width of X)

(New Area) - (Old Area)

(x^2 + 2xy + y^2) - (x^2)

Cancel out the like terms to get a final answer of... :

**Change in Area = 2xy + y^2**Part B:

Same situation as the last problem! Except in this case we will be subtracting y. So our sides now look like this:

X - Y

Area = Base*Height

Both are base and height equal x-y. So we just need to multiply them together like before.

Area = (x - y)^2

Area = (x - y)(x - y)

Multiply the First Terms:

x*x = x^2

Multiply the Outer Terms:

x*-y = -xy

Multiply the Inner Terms:

-y*x = -xy

Multiply the Last Terms:

-y*-y = y^2

**Area = x^2 - 2xy + y^2**Change in Area = x^2 -2xy + y^2 - x^2

Once again the x^2 will cancel out.

**Change in Area = -2xy + y^2**Part C:

This is where it becomes a bit trickier. Now we have a rectangle instead of a square.

So we have two different sides.

I'll note that it doesn't matter if you say the x-y or x+y are the length or the width. As long as they are both represented it is fine.

Area = L*W

Area = (x - y)(x + y)

Multiply the First Terms:

x*x = x^2

Multiply the Outer Terms:

x*y = xy

Multiply the Inner Terms:

-y*x = -xy

Multiply the Last Terms:

-y*y = -y^2

**Area = x^2 + xy - xy + y^2**

The xy's cancel out.Change in Area = x^2 + y^2 - x^2

You can probably guess by now, but the x^2's will cancel out once again!

**Change in Area = y^2**#2: Part A:

(10x^4y^3 + 5x^3y^2 - 15x^2y - 25x^2y^4)/-5x^2y

We need to ask a few questions to get to our answer.

Is the constant in front of the denominator (-5) divisible by all of the constants in front of all the terms in the numerator (10 + 5 - 15 - 25)?

What variables are in the denominator? (x and y are)

Do all of the terms in the numerator have x and y?

If yes, then what is the lowest power of x? (x^2)

If yes, then what is the lowest power of y? (y)

What we have here is what we need to reduce the denominator by.

So we reduce all the constants by -5. (Divide by -5)

10/-5 = -2

5/-5 = -1

-15/-5 = 3

-25/-5 = 5

Next up is the variables.

For these we simply subtract the lowest power from all of them. (In reality we are dividing them by x^2, thus reducing

x^4/x^2 = x^2

x^3/x^2 = x

x^2/x^2 = 1

x^2/x^2 = 1

Lastly the y terms.

Same deal with the x terms.

y^3/y = y^2

y^2/y = y

y/y = 1

y^4/y = y^3

Now put them all together!

**-2x^2 -xy +3 +5y^3**Part B:

All the x terms would be increased by 1 due to being reduce one less power.

So it'll look like this:

**-2x^3 - x^2y + 3 + 5xy^3**Part C:

The Degree is 3, because the highest power is 3 (y^3). The classification for this is a Cubic Polynomial.

### How to solve this math question

(2x - 1) + (x + 4) = 12

2x - 1 + x + 4 = 12

3x + 3 = 12

3x = 12 - 3

3x = 9

x = 3

:)

2x - 1 + x + 4 = 12

3x + 3 = 12

3x = 12 - 3

3x = 9

x = 3

:)

### X^2+10x-7 / x^2+10x+25=0 how do i solve for x?

**You just have to solve the next equation:**

**x²+10x-7=0**

Because, if the numerator is equal to "0", then the next expression

(x²+10x-7) /( x²+10x+25)=0

Therefore:

x²+10x-7=0

x=[-10⁺₋√(100+28)]/2=(-10⁺₋√128)/2=(-10⁺₋8√2)/2=-5⁺₋4√2

We have two possible solutions:

x₁=-5-4√2

x₂=-5+4√2

Now, we have to check these possible solutions.

**Remember the denominator cannot be equal to "0".**

if x=-5-4√2

[(-5-4√2)²+10(-5-4√2)-7] / [(-5-4√2)²+10(-5-4√2)+25]=0/32=0

Therefore: x=-5-4√2 is a solution.

if x=-5+4√2

[(-5+4√2)²+10(-5+4√2)-7] / [(-5+4√2)²+10(-5+4√2)+25]=0/32=0

Therefore: x=-5+4√√2 is a solution.

**Answer: we have two solutions for x:**

**x₁=-5-4√2**

**x₂=-5+4√2**

### Joe solved and justified each step as shown. Identify Joe’s error and fix his mistake. Step Justification Given equation Multiplication Property of Equality Subtraction Property of Equality

I'm still confused can you message me the screen shot of the question?

### Jerry says that if a store has a sale for 35% off and the sale price of a stairmaster is $137, then you can figure out what the original price was by taking 35% of 137 and adding it back onto the $137. So the original price should be $184.95. But that answer doesn't check. Why

Don't know if it's right, but do let me know! use percentage to visualise your workings. :)

### How do I solve for x ?X +8=-15

Solve for x; in order to do that you must subtract 8 from both sides so x is by itself; the answer is -23

### Area and circumference of a circle with a diameter of 2. Use the value 3.14 for pie and do not round your answers.

As much as the above answer is a noble effort it is not correct unfortunately. The value of Pi refers to the number of times that the diameter of a circle will fit into its circumference, and for all circles this is an irrational and infinite number with a value of 3.1415926535... where the numbers continue infinitely and never repeat.

Given that we know that Pi is the number of times the diameter fits into the circumference, we can come up with the formula that:

Pi = circumference/diameter

Now that we know this we can rearrange and substitute your values like so:

Circumference = Pi x Diameter

Circ. = 3.14 x 2 = 6.28

Therefore 6.28 is the circumference of this circle :)

Given that we know that Pi is the number of times the diameter fits into the circumference, we can come up with the formula that:

Pi = circumference/diameter

Now that we know this we can rearrange and substitute your values like so:

Circumference = Pi x Diameter

Circ. = 3.14 x 2 = 6.28

Therefore 6.28 is the circumference of this circle :)

### Choose the statement that best describes the value of 7 4 √ 74 square root of, 74, end square root. Choose 1 answer. Choose 1 answer. The value of 7 4 √ 74 square root of, 74, end square root is between 8 88 and 8 . 5 8.58, point, 5. The value of 7 4 √ 74 square root of, 74, end square root is between 8 . 5 8.58, point, 5 and 9 99. The value of 7 4 √ 74 square root of, 74, end square root is between 9 99 and 9 . 5 9.59, point, 5. The value of 7 4 √ 74 square root of, 74, end square root is between 9 . 5 9.59, point, 5 and 1 0 1010.

Square root of 74? hold on im cofused by all those numbers just give me a moment

### Suppose that prices of a gallon of milk at various stores in one town have a mean of $3.96 with a standard deviation of $0.12. Using Chebyshev's Theorem, what is the minimum percentage of stores that sell a gallon of milk for between $3.72 and $4.20? Round your answer to one decimal place.

**Answer:**

25%

**Step-by-step explanation:**

Given that prices of a gallon of milk at various stores in one town have a mean of $3.96 with a standard deviation of $0.12.

When sales lie between 3.72 and 4.20 dollars we get

we have 3.72 = 3.96-2 (0.12) and

4.20 = 3.96+2(0.12)

Hence simply we can write

i.e. 25% is the minimum percentage of stores that sell a gallon of milk for between $3.72 and $4.20

### Solve. x-3y+2z=1 -x+4y-4z=1 5x-y+6z=9 Write answer in the form (x,y,z).

1x - 3y + 2z = 1 → 1x - 3y + 2z = 1

-1x + 4y - 4z = 1 → -1x + 4y - 4z = 1

5x - 1y + 6z = 9 → y - 2z = 2

1x - 3y + 2z = 1

-1x + 4y - 4z = 1 → -1x + 4y - 4z = 1 → -5x + 20y - 20z = 5

5x - 1y + 6z = 9 → 5x - 2y + 6z = 9 → 5x - 1y + 6z = 9

19y - 14z = 14

y - 2z = 2 → 19y - 38z = 38

19y - 14z = 14 → 19y - 14z = 14

-24z = 24

-24 -24

z = -1

y - 2z = 2

y - 2(-1) = 2

y + 2 = 2

- 2 - 2

y = 0

x - 3y + 2z = 1

x - 3(0) + 2(-1) = 1

x - 0 - 2 = 1

x - 2 = 1

+ 2 + 2

x = 3

(x, y, z) = (3, 0, -1)

-1x + 4y - 4z = 1 → -1x + 4y - 4z = 1

5x - 1y + 6z = 9 → y - 2z = 2

1x - 3y + 2z = 1

-1x + 4y - 4z = 1 → -1x + 4y - 4z = 1 → -5x + 20y - 20z = 5

5x - 1y + 6z = 9 → 5x - 2y + 6z = 9 → 5x - 1y + 6z = 9

19y - 14z = 14

y - 2z = 2 → 19y - 38z = 38

19y - 14z = 14 → 19y - 14z = 14

-24z = 24

-24 -24

z = -1

y - 2z = 2

y - 2(-1) = 2

y + 2 = 2

- 2 - 2

y = 0

x - 3y + 2z = 1

x - 3(0) + 2(-1) = 1

x - 0 - 2 = 1

x - 2 = 1

+ 2 + 2

x = 3

(x, y, z) = (3, 0, -1)

### Suppose that prices of a gallon of milk at various stores in one town have a mean of $3.96 with a standard deviation of $0.12. Using Chebyshev's Theorem what is the minimum percentage of stores that sell a gallon of milk for between $3.72 and $4.20? Round your answer.

75% of the stores that sell milk sell it between $3.72 and $4.20.

Side note that is crazy expensive milk.

Side note that is crazy expensive milk.

### A line passes through (−1, 5) and (1, 3) Which answer is the equation of the line? A.x + 2y = 7 B. x + y = 4 C. x + y = 2 D.x + 2y = 5

I hope this helps you